RF Corporation: 360 flexible stand fan / Muhamad Azrul Nizam Abu Bakar, Mohd Hakem Anas, Moreen Dennis - Abu Bakar, Muhamad Azrul Nizam; Anas, Mohd Hakem; Dennis, Moreen (2017)
This business is based on partnership type of business. It consists a total of three partners that hold significant position in the company which are General and Administration Manager, Marketing and Financial Manager, and Operational Manager. RF Corporations produces a stand fan that can turn 360 degree.